2019
DOI: 10.1103/physrevb.99.155409
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb drag of excitons in Bose-Fermi systems

Abstract: We develop a microscopic theory of the Coulomb drag effect in a hybrid system consisting of spatially separated two-dimensional quantum gases of degenerate electrons and dipolar excitons. We consider both the normal-phase and condensate regimes of the exciton subsystem and investigate the cross-mobility of the system being the kinetic coefficient, which couples the static electric field applied to the electron layer with the particle density current (flux) in the exciton subsystem. We study the temperature dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…systems, where they provide the leading contribution, although in Bose-condensed systems they may be disregarded [29]. However, accounting for the noncondensate diagrams can be important in some cases, as argued, e.g., in Ref.…”
Section: A Additional Diagrams For Rectification Function Of Polaritonsmentioning
confidence: 97%
See 1 more Smart Citation
“…systems, where they provide the leading contribution, although in Bose-condensed systems they may be disregarded [29]. However, accounting for the noncondensate diagrams can be important in some cases, as argued, e.g., in Ref.…”
Section: A Additional Diagrams For Rectification Function Of Polaritonsmentioning
confidence: 97%
“…With the Green functions ( 14), similarly to [29], we write the lowest order contribution of the processes involving the condensate to the rectification function. It is proportional to the density of polariton condensate n p 0 :…”
Section: Polaritonsmentioning
confidence: 99%
“…, where g v is the valley degeneracy factor (1 for QW and 2 for TMDC electronic layer). Following a standard calculation based on the Matsubara technique [2], it can be shown that in a clean system or with uncorrelated disorder potentials in both layers the first order in the expansion of χ el−p ik over the interlayer electron-polariton interaction is zero in the static limit iω → 0, and the leading order is given by the second-order term [29]:…”
Section: Calculation Of Drag Densitymentioning
confidence: 99%
“…Modern two-dimensional materials and heterostructures [25,26] provide a prospective platform for realization of drag effects. Hybrid Bose-Fermi systems with polaronic and drag effects induced by electron-exciton and electron-polariton interactions are especially interesting in this context [27][28][29][30][31]. Formation of polaritons in semiconductor quantum wells and two-dimensional transition metal dichalcogenides embedded into optical microcavities [32] allows to enhance tunability of the Bose-Fermi systems, to increase the critical temperature of Bose-Einstein condensation (BEC) and to employ polaronic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have so far focused on the regime of small exciton concentration where their interaction with electrons leads to the formation of Fermi polarons [11-13, 16, 18, 19]. Increasing the exciton concentration beyond the polaron regime has been predicted to give rise to a range of intriguing phenomena such as trion liquids [20], density ordered, and superconducting phases [21][22][23][24][25][26][27].…”
mentioning
confidence: 99%